Exploring Social and Organizational Support's Role: The Effect of Work-Family Conflict on Work Stress - Rumijati, Aniek; Arifiani, Ratya Shafira (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2024)
AbstractThis study aimed to analyze the effect of work-family conflict on work stress and the moderating role of social support and perceived organizational support in the effect of work-family conflict on work stress. The type of this research is explanatory research. Data collection techniques used were questionnaires and variable measurement techniques based on a Likert scale. The population in this study were all female nurses in Malang City. The sampling technique used is non-probability sampling using purposive sampling, with the criteria of female nurses who are married. Data were analyzed using inferential statistics and a moderation test using Smart PLS. The results of the study revealed that work-family conflict had a significant effect on work stress; social support moderated the effect of work-family conflict on work stress; Perceived organizational support had a moderating role in the effect of work-family conflict on work stress. Keywords:Work-Family Conflict; Work stress; Social Support; Perceived Organizational Support